Note: Physical Properties of High Oleic Sunflower Seeds - Santalla, Estela Mercedes (2003)
High oleic sunflower seeds evaluated at 5.6% moisture content (dry basis) showed a surface area of approximately 102.41 mm2 with an average length, width, thickness and unit mass of 11.526, 5.008 and 2.809 mm and 0.055 g, respectively. Corresponding values for the kernel were 8.802, 3.897 and 1. 907 mm and 0.036 g. The mean equivalent diameter and sphericity of the seeds were 5.49 mm and 0.46, respectively, while corresponding values for the kernels were 4.01 mm and 0.44. True density increased, within a moisture range of 4-26% d.b., between 652 and 708 kg/m3 for the seed, between 1015 and 1057 kg/m3 for the kernel and between 636 and 760 kg/m3 for the hull. The bulk density decreased from 386 to 373 kg/m3 for seeds and from 260 to 220 kg/m3 for hulls and increased from 535 to 553 kg/m3 for the kernels. Porosity increased from 41.2 to 47.1% in seeds, from 47.2 to 47.7% in kernels and from 59.2 to 70.1% in hull. Terminal velocity of seeds increased with moisture content between 2.8 and 5.5 m/s for seed, between 1.8 and 3.8 m/s for kernel and between 1.1 and 1.9 m/s for hull. Drag coefficient decreased when moisture content increased and varied between 4.7 and 1.4 in seed and between 12.5 and 3.1 in kernel. Angle of repose increased with moisture content between 25 and 46° in seeds, between 35 and 55° in kernels and between 49 and 66° in hull on different surfaces and resulted higher for hull and kernel than for seed. The coefficient of static friction was higher for kernel than that for seed and hull and also was higher on wood (with grain perpendicular to the direction of the motion) and lower on acrylic and galvanised iron. This coefficient increased with moisture content from 0.23 to 0.50 for seed, from 0.37 to 0.69 for kernel and from 0.31 to 0.60 for hull. All engineering properties evaluated showed a linear dependence with moisture content, leading to simple and accurate formulae, adequate to predict their variation in the range of moisture considered.